A study on applicability of sound art as therapy for Alzheimer’s patients in institutional cares / Mohammad Kamal Sabran - Sabran, Mohammad Kamal (Institute of Graduate Studies, UiTM, 2018)
In the advance of today’s interdisciplinary research, a new era of art and health science has emerged. New, wider knowledge has given opportunities to artists exploring the use of art and its therapeutic purposes in health care environments. As Alzheimer’s disease increases around the world with still no absolute medication to solve the problem, art has become the alternative treatment. Various studies have shown that art is the only medium that can be perceived positively by Alzheimer’s patients regardless of their remaining abilities and limited skill capacity. Nevertheless, with sound art exploring public spaces to exhibit, and seen as not too distant from conventional art approach such as music therapy, the use of sound art is still not fully utilized to support a healthy environment in Alzheimer’s care centers. This study aims to explore the applicability of sound art as therapy for Alzheimer’s patients. This project has investigated the issues, nature, and reasons that arise through literature reviews, pilot studies, observations and conducted interviews. In particular, it has focused on identifying the potential of sound characteristics, components and elements of sound art making…